Establishing an experimental agenda at the Accademia del Cimento: Carlo Rinaldini's book lists. - Giannini, Giulia (Annals of Science, 2023)
Information on the origins of the Accademia del Cimento is extremely limited. Almost all of the surviving correspondence relating to the year before the Academy began its activities variously concerns print culture. Lists of books (read, studied, purchased, and researched), handwritten notes on old or new publications, vernacular translations of edited passages, and inquiries about new works punctuate the archive. The study of these lists and of the relationship between reading practices and ones related to annotation and knowledge production leads to a reinterpretation of certain aspects of the Accademia del Cimento, suggesting the pursuit of a more flexible agenda. Through the analysis of some book lists, this contribution aims to shed light on the presence in Florence of interconnected groups of scholars, common epistemic practices, and a kind of methodological unity centred on the sharing of materials and agreement concerning the need to subject theories to experimental verification.